Testing marketing expenses role on the relation between leverage and performance - Sri Murni Setyawati; Wita Ramadhanti (Jurnal Keuangan dan Perbankan, 2019)
Marketing expenses usually one of the most important costs for the companies, but still a few research in finance discussing this. The previous study still inconsistent about the role of marketing expenses as a moderator or mediator between the effects of leverage on financial performance. This research intended to empirically test on that subject. This research is using 1792 panel financial report data taken from 256 companies listed in Indonesian Stock Exchange during 2010-2016. There are three main variables in this research: a performance that measures using returns on assets (ROA), marketing expenses are measures using the natural logarithm of marketing expenses. Leverage is calculated using total debt per total asset. Data is analyzed using panel data regression. The results show that marketing expense is a moderator but not a mediator variable in the effect of leverage on financial performance. Marketing expense moderates negatively the relationship between financial leverage on ROA. This is consistent with strategic management using Resources Advantage Theory and Du Pont Business Model.JEL Classification: G32, M31DOI: https://doi.org/10.26905/jkdp.v23i3.3208